Dengue in the campus community of an overseas American university: A cross-sectional study - Hamish Mohammed; Mary H Hayden; Elise Lee; Luis M Santiago; Rosina C Krecek; Floyd Revan; Elizabeth Hunsperger (Journal of Infection in Developing Countries)
Introduction: After a large outbreak of dengue virus (DENV) serotype-3 in Saint Kitts and Nevis (SKN) in 2008, we performed a cross-sectional study to determine the prevalence of anti-DENV immunoglobulin G (IgG) antibodies in expatriate and local persons affiliated with an American veterinary school there.